Factor Analysis of The Influence of Promotions, Product Quality, Service Quality, Brand Awareness, And Communication on Purchase Interest in Food Catering Businesses - Salma Dzikriyah Zulfaa; Tiara Verita Yastica; Sheila Amalia Salma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Sakinah Tegal Restaurant is a catering business that has experienced unstable revenue over the past 10 months. Several factors, such as promotion, product quality, service quality, brand awareness, and communication, affect consumer purchase intention. This study aims to evaluate the effect of these factors on purchase intention in this catering business. The research method used was descriptive quantitative, and data analysis was conducted using the Structural Equation Modelling Partial Least Square (PLS-SEM) method with a sample of 140 respondents. The study results showed an R-square value of 0.830, indicating that promotion, product quality, service quality, brand awareness, and communication together affect purchase intention by 83%. In comparison, the remaining 17% is affected by other variables not examined in this research. Keywords: Catering, PLS-SEM, Consumer Behavior, Marketing Strategy, Promotion, Product Quality, Service Quality, Brand Awareness, Communication, Purchase Intention.